Thermoacoustic measurements during cure of epoxy resin at room temperature - Yoon, H.N.; Yoon, C.N.; Kim, H.C. (1991)
Dynamic thermoacoustic measurements were used to observe the curing of epoxy resin. Measurements were made at the modulation frequency (20 Hz) as a function of time. A twostep increase of the thermoacoustic signal output was notable and could be explained in terms of the transitions liquid → rubber → glass. Copyright ？ 1991 John Wiley & Sons, Inc.
Keywords: Acoustic Variables Measurement; Polymers - Phase Transitions; Thermal Variables Measurement; Dynamic Thermoacoustic Measurements; Thermoacoustic Signals; Epoxy Resins